Development of the ventricular myocardial trabeculae in Scyliorhinus canicula (Chondrichthyes): evolutionary implications - López-Unzu, Miguel A.; Durán-Boyero, Ana Carmen; Rodríguez, Cristina; Soto-Navarrete, María Teresa; Sans-Coma, Valentín; Fernández-Corujo, Borja (Springer, 2020)
The development of the ventricular myocardial trabeculae occurs in three steps: emergence, trabeculation and remodeling. The whole process has been described in vertebrates with two different myocardial structural types, spongy (zebrafish) and compact (chicken and mouse). In this context, two alternative mechanisms of myocardial trabeculae emergence have been identified: (1) in chicken and mouse, the endocardial cells invade the two-layered myocardium; (2) in zebrafish, cardiomyocytes from the monolayered myocardium invaginate towards the endocardium. Currently, the process has not been studied in detail in vertebrates having a mixed type of ventricular myocardium, with an inner trabecular and an outer compact layer, which is presumptively the most primitive morphology in gnathostomes. We studied the formation of the mixed ventricular myocardium in the lesser spotted dogfish (Scyliorhinus canicula, Elasmobranchii), using light, scanning and transmission electron microscopy. Our results show that early formation of the mixed ventricular myocardium, specifically the emergence and the trabeculation steps, is driven by an endocardial invasion of the myocardium. The mechanism of trabeculation of the mixed ventricular myocardium in chondrichthyans is the one that best reproduces how this developmental process has been established from the beginning of the gnathostome radiation. The process has been apparently preserved throughout the entire group of sarcopterygians, including birds and mammals. In contrast, teleosts, at least those possessing a mostly spongy ventricular myocardium, seem to have introduced notable changes in their myocardial trabeculae development.
Keywords: Válvulas cardíacas; Trabeculation; Cardiac ventricle; Myocardium; Evolution; Gnathostomes; Vertebrates